Effect on Reduction in Inflammatory Fluid and Improvement of Cell Membrane/Skeletal Muscle by Far-Infrared Rays Emitted from Loess Bio-Balls During Sleep - Yong Il Shin; Min Seok Kim; Yeong Ae Yang; Yun Jeong Lee; Gye Rok Jeon; Jae Ho Kim; Yeon Jin Choi; Woo Cheol Choi; Jae Hyung Kim (Biomedicines)
Background: Far infrared rays (FIR) can promote microcirculation of blood in capillaries and reduce inflammation and edema by improving lymphatic circulation. Although the short-term therapeutic use of FIR is increasingly common in clinical settings, its effects on inflammatory fluids during sleep are not yet well established. Methods: This was a small-scale exploratory study conducted on patients exhibiting early symptoms of edema or swelling, or participants who reported discomfort possibly due to such symptoms. Changes in impedance parameters related to inflammatory body fluids were measured in subjects (n = 55) lying lay on either a conventional electric mat (non-FIR) or a loess bio-ball mat (FIR) set at 40 °C for 30 min. To assess the effects of heat and FIR exposure during sleep, additional impedance measurements were taken in subjects (n = 60) who used either on an electric mat or a loess bio-ball mat set at 30 °C during sleep. Results: A total of 115 participants were included in four experimental conditions. In subjects exposed to conductive heat or FIR for 30 min while lying on an electric mat and a loess bio-ball mat set at 40 °C, only minimal changes were observed in impedance parameters and inflammatory fluid-related values. However, significant changes were seen in subjects (n = 30) who slept for 7 h on a loess bio-ball mat set at 30 °C. These changes are presumed to results from the deeper sleep and FIR emitted from the loess bio-balls. In contrast, no significant changes were observed in the group (n = 30) that used the electric mat at 30 °C under the same sleep conditions. Conclusions: Sleeping on a FIR-emitting loess bio-ball mat may stimulate biological tissues and lymphatic circulation, gradually reducing inflammatory fluid accumulation. This suggest potential benefits for improving the physiological condition and function of cell membranes and muscles.